Prevalence of Escherichia coli O157 and O157:H7-infecting bacteriophages in feedlot cattle feces - Oot, Rebecca (2007)
Aim: To estimate the distribution and prevalence of both Escherichia coli O157 and O157:H7-infecting bacteriophages within a 50 000 head commercial beef feedlot. Methods and Results: Escherichia coli O157 was detected in ∼27% of the individual samples, distributed across seven of the 10 pens screened. In a simple initial screen to detect O157:H7-infecting phages, none were detected in any pen or individual sample. In contrast, after a series of enrichment procedures O157:H7-infecting phages were detected in every pen and in the majority of the samples from most pens; virulent bacteriophages active against E. coli O157:H7 were detected post-enrichment from 39/60 (65%) of the feedlot samples, and 58/60 (∼97%) contained phage that infected E. coli B or O157:H7. Conclusions: The data we present here indicates that we may be grossly underestimating the prevalence of O157:H7-infecting phages in livestock if we simply screen samples and that enrichment screening is required to truly determine the presence of phages in these ecosystems. Significance and Impact of the Study: Our data suggest that O157:H7-infecting phages may play a role in the ecology and transient colonization of cattle by E. coli O157:H7. Further, this and previous data suggest that before starting in vivo pathogen eradication studies using phage or any other regime, test animals should be enrichment screened for phage to avoid erroneous results.